UNIQUE eCRF – IMPORTANCE TO CLINICAL TRIALS AND HUMAN HEALTH - Gill, Supreet K; Christopher, Ajay F; SANJIV KUMAR; Gupta, Vikas; Bansal, Parveen (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Unique eCRF is a platform in which electronically maintained information about an individual's lifetime health status and health care records can be stored such that it can serve multiple legitimate users and along with serving as case report form of patients in clinical trials. Through Unique eCRF individuals can access, manage and share their health information with others who are authorized, in a private, secure, and confidential environment. Unique e-CRF has potential of integrating various domains of clinical trial like data capture, data cleaning, and data mining into one system and hence significantly contributes in clinical trial management. It also contributes in huge saving of a pharmaceutical company in terms of cost and time. Electronic CRFs offer advantages such as improved data quality, online discrepancy management and faster database lock.The other potential advantages include integrated patient's health and financial data, audit trial capabilities, identifying eligible patients for clinical trials from patient's records, trial randomisation, agile data transfer, follow patient outcomes, in creating patient registries, monitoring adverse drug reactions and pharmacovigilance reporting. Unique eCRF deserve a serious look because they are the most efficient way to connect patients to their medical data. They not only facilitate information sharing among doctors and guard against needless medical errors, but also offer a safety advantage in that health record would never again need to be stored. All eCRFs should be validated in compliance to 21 CFR Part 11.